Pengaruh Celebrity Endorser, Citra Merek, dan Promosi Penjualan terhadap Keputusan Pembelian pada Produk Scarlett Whitening (Studi Kasus Konsumen Scarlett Whitening di Kota Surabaya) - Uchtisyah Alifyanti; Lia Nirawati; Sonja Andarini; Rusdi Hidayat Nugroho (Universitas Batanghari, 2022)
The purpose of this research is to find out and analyze the influence of Celebrity Endorser, Brand Image, and Sales Promotion on Purchase Decisions on Scarlett Whitening products in Surabaya. The approach used in this research is descriptive quantitative approach. The technique used in determining the sample uses a non-probability sampling technique with a purposive sampling method, namely the determination of the sample based on the criteria of Surabaya residents who have used Scarlett Whitening. The method used in collecting data is using a questionnaire in Google Form. The measurement scale used is the Likert scale. Respondents in this study amounted to 101 Scarlett Whitening consumers in Surabaya. The results of the study there is a partial effect of each independent variable on the dependent variable. This study also shows that the variables Celebrity Endorser, Brand Image, and Sales Promotion Simultaneously have a positive and significant effect on purchasing decisions..